The Concept of Scientific Bases of Management - E. M. Korotkov (Управление)
The development of science and education is accompanied by the emergence of the need to incorporate the new knowledge that arises naturally in the theory and practice of economics. In higher education this is manifested by the inclusion of new disciplines in the educational program, the creation of new departments, ensuring the teaching of these disciplines. We need a convincing rationale for the selection of a new discipline, development of its content that reflects practical needs for new knowledge and their scientific significance, scientific basis. The chair of scientific basis of production management, which was formed at the initiative of the rector of the Moscow engineering and economic Institute, doctor of economic Sciences, Professor Kozlova Olympiada V., in the sixties, had to solve these problems. This amounted to a great and difficult work of formation of the concept of management as a new scientific direction in the prevailing complex social and economic sciences, reflecting both the needs of production development and trends in the development of scientific thought.